Systemic Delivery of Bone Marrow Mesenchymal Stem Cells for In Situ Intervertebral Disc Regeneration. (11th October 2016) - Cunha, Carla; Almeida, Catarina R.; Almeida, Maria Inês; Silva, Andreia M.; Molinos, Maria; Lamas, Sofia; Pereira, Catarina L.; Teixeira, Graciosa Q.; Monteiro, António T.; Santos, Susana G.; Gonçalves, Raquel M.; Barbosa, Mário A.
Abstract: Cell therapies for intervertebral disc (IVD) regeneration presently rely on transplantation of IVD cells or stem cells directly to the lesion site. Still, the harsh IVD environment, with low irrigation and high mechanical stress, challenges cell administration and survival. In this study, we addressed systemic transplantation of allogeneic bone marrow mesenchymal stem cells (MSCs) intravenously into a rat IVD lesion model, exploring tissue regeneration via cell signaling to the lesion site. MSC transplantation was performed 24 hours after injury, in parallel with dermal fibroblasts as a control; 2 weeks after transplantation, animals were killed. Disc height index and histological grading score indicated less degeneration for the MSC-transplanted group, with no significant changes in extracellular matrix composition. Remarkably, MSC transplantation resulted in local downregulation of the hypoxia responsive GLUT-1 and in significantly less herniation, with higher amounts of Pax5+ B lymphocytes and no alterations in CD68+ macrophages within the hernia. The systemic immune response was analyzed in the blood, draining lymph nodes, and spleen by flow cytometry and in the plasma by cytokine array. Results suggest an immunoregulatory effect in the MSC-transplanted animals compared with control groups, with an increase in MHC class II+ and CD4+ cells, and also upregulation of the cytokines IL-2, IL-4, IL-6, and IL-10, and downregulation of the cytokines IL-13 and TNF-α. Overall, our results indicate a beneficial effect of systemically transplanted MSCs on in situ IVD regeneration and highlight the complex interplay between stromal cells and cells of the immune system in achieving successful tissue regeneration.